K‐Ar illite age constraints on the Proterozoic formation and reactivation history of a brittle fault in Fennoscandia. (23rd February 2013) - Viola, Giulio; Zwingmann, Horst; Mattila, Jussi; Käpyaho, Asko
Abstract K‐Ar ages of authigenic illite from two drill‐core gouge samples of a fault in the Palaeoproterozoic basement of Finland record two distinct faulting events. The older sample yields apparent ages from 1240 ± 26 to 1006 ± 21 Ma for four grain size fractions between 6 and <0.1 μm. The second sample is structurally younger and yields statistically distinct ages ranging from 978 ± 20 to 886 ± 18 Ma. We interpret the ages of the <0.1 m fractions, which are the youngest, as representing the actual time of faulting. XRD analysis and age modelling exclude significant age contamination of the finest dated fractions with inherited host rock components. These results provide therefore an example of meaningful isotopic dating of illite‐type clay material formed during Precambrian faulting, demonstrate and constrain fault reactivation and give evidence for brittle Sveconorwegian Mesoproterozoic shortening and Neoproterozoic extension in Fennoscandia.